Metaphor in the science language of economists (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is devoted to revealing of the specific features of metaphor in scientific and educational economic texts. The theories of metaphor in historical aspect are considered. The metaphorical models in scientific terminology of economists are analyzed. The functions of metaphor in scientific style of language are defined.
Keywords: metaphor; metaphorization; conceptual metaphor; economic text metaphorical model; economic term